2013
DOI: 10.1038/ncb2874
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitylation and stabilization of PTEN by USP13

Abstract: The tumor suppressor PTEN is frequently lost in human cancers. In addition to gene mutations and deletions, recent studies have revealed the importance of post-translational modifications, such as ubiquitination, in the regulation of PTEN stability, activity and localization. However, the deubiquitinase that regulates PTEN poly-ubiquitination and protein stability remains unknown. Here we screened a total of 30 deubiquitinating enzymes (DUBs) and identified five DUBs that physically associate with PTEN. One of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
156
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 38 publications
7
156
1
Order By: Relevance
“…Down-53 regulation of NEDD4-1 via SCFβ-TRCP-mediated degradation inhibited 54 tumorigenesis through enhancing PTEN function [4]. Deubiquitination 55 of PTEN by USP13, a deubiquitinating enzyme, stabilized PTEN, and 56 thereby inhibited breast cancer tumorigenesis [5]. Conversely, by pro-57 moting NEDD4-1-mediated PTEN polyubiquitination, a 34 kDa protein, 58 p34SEI-1 exhibited oncogenic activities [6,7].…”
Section: Sipl1-facilitated Pten Ubiquitination Contributes To Its Assmentioning
confidence: 99%
“…Down-53 regulation of NEDD4-1 via SCFβ-TRCP-mediated degradation inhibited 54 tumorigenesis through enhancing PTEN function [4]. Deubiquitination 55 of PTEN by USP13, a deubiquitinating enzyme, stabilized PTEN, and 56 thereby inhibited breast cancer tumorigenesis [5]. Conversely, by pro-57 moting NEDD4-1-mediated PTEN polyubiquitination, a 34 kDa protein, 58 p34SEI-1 exhibited oncogenic activities [6,7].…”
Section: Sipl1-facilitated Pten Ubiquitination Contributes To Its Assmentioning
confidence: 99%
“…A recent study, through a screen of 30 USP members, identified USP13 as a candidate that de-polyubiquitylates and stabilizes PTEN (ref. 24). However, depletion of USP13 in cells reduced but did not abolish the PTEN ubiquitylation 24 , suggesting that other DUB(s) might exist to function as the DUB for PTEN.…”
mentioning
confidence: 95%
“…24). However, depletion of USP13 in cells reduced but did not abolish the PTEN ubiquitylation 24 , suggesting that other DUB(s) might exist to function as the DUB for PTEN. It is not surprising that such an important tumour suppressor is controlled by multiple DUBs.…”
mentioning
confidence: 95%
“…2008), whereas USP13 removes polyubiquitin from and thereby stabilizes PTEN (Zhang et al . 2013). The different subcellular localizations of these DUBs—USP7 in the nucleus and USP13 in the cytosol—may allow the targeting of different populations of ubiquitylated PTEN, a scenario that is again reminiscent of p53 regulation by DUBs.…”
Section: Regulation Of Pten By Monoubiquitylationmentioning
confidence: 99%